Accuracy of vertical height measurements on direct digital panoramic radiographs using posterior mandibular implants and metal balls as reference objects - Vazquez, L (The British Institute of Radiology., 2013)
OBJECTIVES: Conventional panoramic radiography, a widely used radiographic examination tool in implant treatment planning, allows evaluation of the available bone height before inserting posterior mandibular implants. Image distortion and vertical magnification due to projection geometry is well described for rotational panoramic radiographs. To assess the accuracy of vertical height measurements on direct digital panoramic radiographs, implants and metal balls positioned in the posterior mandible were used as radio-opaque reference objects. The reproducibility of the measuring method was assessed by the inter- and intraobserver agreements. METHODS: Direct digital panoramic radiographs, performed using a Kodak 8000C (Eastman Kodak Company, Rochester, NY), of 17 partially edentulous patients (10 females, 7 males, mean age 65 years) were selected from an X-ray database gathered during routine clinical evaluation of implant sites. Proprietary software and a mouse-driven calliper were used to measure the radiological length of 25 implants and 18 metal reference balls, positioned in mandibular posterior segments. The distortion ratio (DR) was calculated by dividing the radiological implant length by the implant's real length and the radiological ball height by the ball's real height. RESULTS: Mean vertical DR was 0.99 for implants and 0.97 for balls, and was unrelated to mandibular sites, side, age, gender or observer. Inter- and intraobserver agreements were acceptable for both reference objects. CONCLUSIONS: Vertical measurements had acceptable accuracy and reproducibility when a software-based calibrated measurement tool was used, confirming that digital panoramic radiography can be reliably utilized to determine the pre-operative implant length in premolar and molar mandibular segments.